The mechanism of HMGB1 secretion and release - Chen, Ruochan; Kang, Rui; Tang, Daolin (Experimental & molecular medicine, 2022)
High mobility group box 1 (HMGB1) is a nonhistone nuclear protein that has multiple functions according to its subcellular location. In the nucleus, HMGB1 is a DNA chaperone that maintains the structure and function of chromosomes. In the cytoplasm, HMGB1 can promote autophagy by binding to BECN1 protein. After its active secretion or passive release, extracellular HMGB1 usually acts as a damage-associated molecular pattern (DAMP) molecule, regulating inflammation and immune responses through different receptors or direct uptake. The secretion and release of HMGB1 is fine-tuned by a variety of factors, including its posttranslational modification (e.g., acetylation, ADP-ribosylation, phosphorylation, and methylation) and the molecular machinery of cell death (e.g., apoptosis, pyroptosis, necroptosis, alkaliptosis, and ferroptosis). In this minireview, we introduce the basic structure and function of HMGB1 and focus on the regulatory mechanism of HMGB1 secretion and release. Understanding these topics may help us develop new HMGB1-targeted drugs for various conditions, especially inflammatory diseases and tissue damage. Inflammation: Nuclear protein offers target for controlling immune response A nuclear protein that gets released after cell death or is actively secreted by immune cells offers a promising therapeutic target for treating diseases linked to excessive inflammation. Daolin Tang from the University of Texas Southwestern Medical Center in Dallas, USA, and colleagues review how cellular stresses can trigger the accumulation of HMGB1, a type of alarm signal protein that promotes the recruitment and activation of inflammation-promoting immune cells. The researchers discuss various mechanisms that drive both passive and active release of HMGB1 into the space around cells. These processes, which include enzymatic modifications of the HMGB1 protein, cell–cell interactions and molecular pathways of cell death, could be targeted by drugs to lessen tissue damage and inflammatory disease caused by HMGB1-induced immune responses